Studi potensi hutan mangrove di Pulau Serangan sebagai kawasan ekowisata - Artha, I Ketut Darma Kusuma; Utami, Ni Wayan Febriana; Gunadi, I Gusti Alit (Jurnal Arsitektur Lansekap, 2019)
Study on the potency of mangroves forest in Serangan Island as ecotourism area in South Denpasar District, Denpasar, Bali. Mangrove Forest on Serangan Island is an area managed by PT.Bali Turtle Island Development (BTID) which is a government land under the supervision of the Bali Provincial Forestry Agency (Dinas Kehutanan Provinsi Bali) and Nature Resource Conservation Center (BKSDA). The total area of mangrove forest about of 33 hectares, the mangrove forest in Serangan Island indicate to have biophysic potency such diversity of mangrove species and diversity of fauna. The purpose of this study is to identify the biodiversity of mangrove forests and to assess the suitability of mangrove forests as ecotourism areas. The method used in this research was the conformity analysis proposed by Bahar (2004) and Yulianda (2007) to assess the potency of mangrove forest with biophysical approach. The results of this study found that the area of mangrove forest on Serangan Island was dominated by mangrove species Sonneratia and Rhizopora, with diversity of fauna found such as birds, reptiles, and marine biota at each point of observation area. The tourist suitability index (Ik) of mangrove forest was 153 and belong to medium category or potentially as an ecotourism area. Recommendation for ecotourism development area of mangrove forest consist of basic concept of development which were buffer area and eco-tourism area. Then ecotourism activities were develop e.g natural interpretation, nature viewing, bird watching, photo hunting, board walks, and fishing. In addition, support from local community and tourists around the mangrove forest was very much to developed Serangan Island as an ecotourism area.